Provider‐to‐provider electronic communication in the era of meaningful use: A review of the evidence. Issue 10 (4th October 2013) - Walsh, Colin; Siegler, Eugenia L.; Cheston, Erin; O'Donnell, Heather; Collins, Sarah; Stein, Daniel; Vawdrey, David K.; Stetson, Peter D.; ,
<x xml:space="preserve">Abstract</x> BACKGROUND Electronic communication between providers occurs daily in clinical practice but has not been well studied. PURPOSE To assess the impact of provider‐to‐provider electronic communication tools on communication and healthcare outcomes through literature review. DATA SOURCES Ovid MEDLINE, PubMed, Google Scholar, Cumulative Index to Nursing and Allied Health Literature, and Academic Search Premier. STUDY SELECTION Publication in English‐language peer‐reviewed journals. Studies provided quantitative provider‐to‐provider communication data, provider satisfaction statistics, or electronic health record (EHR) communication data. DATA EXTRACTION Literature review. DATA SYNTHESIS Two reviewers conducted the title review to determine eligible studies from initial search results. Three reviewers independently reviewed titles, abstracts, and full text (where appropriate) against inclusion and exclusion criteria. LIMITATIONS Small number of eligible studies; few described trial design (20%). Homogeneous provider type (physicians). English‐only studies. CONCLUSIONS Of 25 included studies, all focused on physicians; most were observational (68%). Most (60%) described electronic specialist referral tools. Although overall use has been measured, there were no studies of the effectiveness of intra‐EHR messaging. Literature describing the effectiveness of provider‐to‐provider electronic communications is sparse and narrow in scope. Complex care, such as that envisioned for the Patient Centered Medical Home, necessitates further research. Journal of Hospital Medicine 2013;8:589–597. © 2013 Society of Hospital Medicine